2015
DOI: 10.3758/s13414-015-0860-2
|View full text |Cite
|
Sign up to set email alerts
|

The long and the short of priming in visual search

Abstract: Memory affects visual search, as is particularly evident from findings that when target features are repeated from one trial to the next, selection is faster. Two views have emerged on the nature of the memory representations and mechanisms that cause these intertrial priming effects: independent feature weighting versus episodic retrieval of previous trials. Previous research has attempted to disentangle these views focusing on short term effects. Here, we illustrate that the episodic retrieval models make th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 61 publications
(97 reference statements)
9
46
2
Order By: Relevance
“…Intriguingly, the pool model that Taatgen and Van Rijn proposed as an account for these effects is based on principles of memory storage similar to those of MTP. Finally, in the more distant domain of visual search, it has been observed that selection is faster when target features are repeated from one trial to the next, and in the case of conjunction search these effects even occur on the long term, that is, up to at least a week, as in the present experiment (Kruijne & Meeter, 2015, 2016.…”
Section: Discussionsupporting
confidence: 61%
“…Intriguingly, the pool model that Taatgen and Van Rijn proposed as an account for these effects is based on principles of memory storage similar to those of MTP. Finally, in the more distant domain of visual search, it has been observed that selection is faster when target features are repeated from one trial to the next, and in the case of conjunction search these effects even occur on the long term, that is, up to at least a week, as in the present experiment (Kruijne & Meeter, 2015, 2016.…”
Section: Discussionsupporting
confidence: 61%
“…More recent work using target identification tasks has extended the target frequency effect to situations in which one of two targets is always present. The more frequent target stimulus is detected more rapidly (Kruijne & Meeter, 2015). These findings firmly establish target frequency as a modulator of attentional priority.…”
Section: Introductionsupporting
confidence: 64%
“…However, in a color singleton search task in which the target was more often one color (e.g., red among green) rather than another (e.g., green among red), the frequency effect dissipated quickly. This was the case even when the singleton search task was difficult (Kruijne & Meeter, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this process of information extraction from maps is initiated and surrounded by a personal, emotional context. Since emotion and cognition are interlaced aspects and the visual search for information acquisition is influenced by mood and memory (Kruijne & Meeter, 2015;Storbeck & Clore, 2005), this research aims at determining the effects of valence on selecting and memorizing spatial information from road maps (e.g. google maps).…”
mentioning
confidence: 99%